Failure-to-rescue in patients undergoing surgery for esophageal or gastric cancer. Issue 10 (October 2017) - Busweiler, L.A.; Henneman, D.; Dikken, J.L.; Fiocco, M.; van Berge Henegouwen, M.I.; Wijnhoven, B.P.; van Hillegersberg, R.; Rosman, C.; Wouters, M.W.; van Sandick, J.W.; ,
Abstract: Background: Complex surgical procedures such as esophagectomy and gastrectomy for cancer are associated with substantial morbidity and mortality. The purpose of this study was to evaluate trends in postoperative morbidity, mortality, and associated failure-to-rescue (FTR), in patients who underwent a potentially curative resection for esophageal or gastric cancer in the Netherlands, and to investigate differences between the two groups. Methods: All patients with esophageal or gastric cancer who underwent a potentially curative resection, registered in the Dutch Upper GI Cancer Audit (DUCA) between 2011 and 2014, were included. Primary outcomes were (major) postoperative complications, postoperative mortality and FTR. To investigate groups' effect on the outcomes of interest a mixed model was used. Results: Overall, 2644 patients with esophageal cancer and 1584 patients with gastric cancer were included in this study. In patients with gastric cancer, postoperative mortality (7.7% in 2011 vs. 3.8% in 2014) and FTR (38% in 2011 and 19% in 2014) decreased significantly over the years. The adjusted risk of developing a major postoperative complication was lower (OR 0.54; 95% CI 0.42–0.70), but the risk of FTR was higher (OR 1.85; 95% CI 1.05–3.27) in patients with gastric cancer compared to patients with esophageal cancer. Conclusion: Once a postoperative complication occurred, patients with gastric cancer were more likely to die compared to patients with esophageal cancer. Underlying mechanisms like patient selection, and differences in structure and organization of care should be investigated. Next to morbidity and mortality, failure-to-rescue should be considered as an important outcome measure after esophagogastric cancer resections.